Technology-enabled learning (TEL) policy of Universiti Malaysia Sabah: a learner’s perspective - Jamsari Hashim; Anna Lynn Abu Bakar (Pusat Penataran Ilmu Bahasa, Universiti Malaysia Sabah, 2020)
Technology-Enabled Learning (TEL) Policy UMS aims to provide a framework to consolidate Technology-Enabled Learning at the university and to envisage improvement in the quality of Teaching and Learning (T&L) via the use of technology where the sharing of educational resources was conceptualized by the Centre for E-Learning, Centre for Teaching Excellence and Academic Quality (PKPKA), and Department of Information Technology & Communication (JTMK). It is an output of a workshop which was conducted on 19 & 20 March 2018 in the Auditorium Centre of Post Graduate Studies attended by the management and e-Learning Coordinators of JFPIU and subsequently approved by the University Senate/LPU. The objective of this research is to systematically examine the word ‘learning’ contextualised from the learner’s point of view in (1) the vision of TEL policy in UMS and (2) policy statements concerning technology and infrastructure; teaching, learning and assessment; professional development; and governance. The method employed in this research was a six steps content analysis by Ball and Smith (1992) in Abercrombie & Longhurst (2007). The result of this research produced 10 themes of the word ‘learning’ in TEL Policy. As a conclusion, this research has achieved its objective as postulated.